Identification Of Microorganism Composition In Indigenous Microorganisms (Imo) Solutions Of Various Fruit Peels And Their Utilization In Organic Peanut Cultivation - Elisabeth Sri Pujiastuti; Juli Ritha Tarigan; Yanto Raya Tampubolon; Ferlist Rio Siahaan; Susana Tabah Trina Sumihar (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2022)
This paper consists of two researches. A research to identify the microbial composition and density of various types of indigenous microorganisms (IMO) solutions was carried out descriptively. Another research aimed to study the effect of the types of IMO on the growth and yield of peanut was carried out using a randomized block design with three replications and two treatment factors, namely the types of IMO consisting of IMO of tamarillo, pineapple and orange peels, and the dose of chicken manure with the levels of 0, 10, 20 and 30 tons/ha. The IMOs were applied at a concentration of 45 ml/liter, each. The results showed that the IMO of tamarillo, pineapple and orange peels contained different densities of at least six types of microbes, namely: Pseudomonas sp; Azotobacter sp; Bacillus sp; Actinomycetes sp; Streptomyces sp and P (phosphate) solubilizing microbes, but the type of IMO had no significant effect on plant height and stem diameter at 6 WAP as well as the number of filled pods and the yield per plot. The three types of IMO gave the same good effect, as indicated by the production of 197 percent compared to the yield potential of Gajah variety.